2014
DOI: 10.5750/ejpch.v2i4.812
|View full text |Cite
|
Sign up to set email alerts
|

A 30-month follow-up of generalized anxiety disorder: Status after metacognitive therapy and intolerance of uncertainty-therapy

Abstract: Objectives: Although metacognitive therapy and intolerance-of-uncertainty therapy are considered efficacious treatments for generalized anxiety disorder, little is known about the long-term course in patients who engaged in treatment studies. Method: We conducted a continuation study of patients with GAD who had participated in a randomized, delayed treatment controlled trial in which the relative efficacy of MCT and IUT were compared.Results: Of the original 85 patients who completed the study, 34 were availa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…The mean length of the included follow-up periods was 8.2 months from post-treatment (standard deviation 5.9, range 3–24 months). As displayed in Figure 1 , we excluded one publication (van der Heiden and Melchior, 2014 ), which was a 30-month follow-up of an included trial (van der Heiden et al, 2012 ), as the publication reported on 34 out of the original 126 participants. We further chose not to include the follow-up data in another study (van der Heiden et al, 2013 ), as the authors had not included the data in their primary analysis due to a large dropout rate.…”
Section: Resultsmentioning
confidence: 99%
“…The mean length of the included follow-up periods was 8.2 months from post-treatment (standard deviation 5.9, range 3–24 months). As displayed in Figure 1 , we excluded one publication (van der Heiden and Melchior, 2014 ), which was a 30-month follow-up of an included trial (van der Heiden et al, 2012 ), as the publication reported on 34 out of the original 126 participants. We further chose not to include the follow-up data in another study (van der Heiden et al, 2013 ), as the authors had not included the data in their primary analysis due to a large dropout rate.…”
Section: Resultsmentioning
confidence: 99%
“…A study on 30‐month follow‐up for MCT and intolerance of uncertainty therapy (IUT; van der Heiden & Melchior, 2014 ) reported a recovery rate of 75% for MCT and 50% for IUT. However, the study used different criteria for recovery (cut‐off point ≤ 53; reliable change index ≥ 7).…”
Section: Discussionmentioning
confidence: 99%
“…The superiority of MCT was observed over follow‐up periods in these initial studies that ranged from 6 to 24 months. Van der Heiden and Melchior ( 2014 ) conducted a 30‐month follow‐up of patients treated in their trial. They showed that both MCT and CBT patients maintained their gains during the interim period from 6‐month to 30‐month follow‐up, with MCT producing a significantly better outcome at 30‐month follow‐up as evidenced by a large between‐group effect ( d = 1.16) and higher recovery rate (75% vs. 50%).…”
Section: Introductionmentioning
confidence: 99%